Photosynthesis, Chlorophyll Fluorescence, and Yield of Peanut in Response to Biochar Application - Wang, Shujun; Zheng, Junlin; Wang, Yujia; Yang, Qingfeng; Chen, Taotao; Chen, Yinglong; Chi, Daocai; Xia, Guimin; Siddique, Kadambot H.M.; Wang, Tieliang (Frontiers in Plant Science, 2021)
The effect of biochar application on photosynthetic traits and yield in peanut (Arachis hypogaea L.) is not well understood. A two-year field experiment was conducted in Northwest Liaoning, China to evaluate the effect of biochar application [0, 10, 20, and 40 t ha–1 (B0, B10, B20, and B40)] on leaf gas exchange parameters, chlorophyll fluorescence parameters, and yield of peanut under supplemental irrigation. B10 improved photochemical quenching (qP) at flowering and pod set and reduced non-photochemical quenching (NPQ) at pod set, relative to B0. B10 and B20 increased actual photochemical efficiency (ΦPSII) and decreased regulated energy dissipated (ΦNPQ) at pod set, relative to B0. B10 significantly increased net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), and water use efficiency (WUE) at flowering and pod set, relative to B0. Compared with B0, B10 significantly improved peanut yield (14.6% and 13.7%) and kernel yield (20.2% and 14.4%). Biochar application increased leaf nitrogen content. B10 and B20 significantly increased plant nitrogen accumulation, as compared to B0. The net photosynthetic rate of peanut leaves had a linear correlation with plant nitrogen accumulation and peanut yield. The application of 10 t ha–1 biochar produced the highest peanut yield by enhancing leaf photosynthetic capacity, and is thus a promising strategy for peanut production in Northwest Liaoning, China.